Common identity framework of cultural knowledge and practices of Javanese Islam - Sulistiyono Susilo; Ibnu Syato (IAIN Salatiga, 2016)
Previous literatures apparently argued that Javanese Islam is characterized by orthodox thought and practice which is still mixed with pre-Islamic traditions. By using approach of the sociology of religion, this article tries to explain contextualization of Islamic universal values in local space. The results showed that synthesis of orthodox thought and practice with pre-Islamic traditions is doubtless as a result of interaction between Islam and pre-Islamic traditions during the Islamization of Java. In addition, this study found the intersection of Islam and Javanese culture in the terms of genealogy of culture, Islamic mysticism, orientation of traditional Islamic teachings, and the conception of the power in Javanese kingdom. Since kejawen practices accordance with Islamic mysticism can be justified by the practice of the Muslims. Thus the typology of the relationship between Islam and Javanese culture are not contradictory but dialectical. Finally, a number of implications and suggestions are discussed Berbagai literatur sebelumnya mengenai studi Islam di Jawa umumnya berpendapat bahwa Islam Jawa ditandai dengan pemikiran dan praktek yang masih tercampur dengan tradisi pra-Islam. Dengan menggunakan pendekatan sosiologi agama, artikel ini mencoba untuk menjelaskan makna dari kontekstualisasi nilai-nilai universal Islam pada lingkup lokal. Hasil penelitian menunjukkan bahwa sintesis pemikiran dan praktek dengan tradisi pra-Islam merupakan hal yang lumrah sebagai hasil interaksi antara Islam dan tradisi praIslam selama periode Islamisasi. Penelitian ini menemukan persamaan identitas antara Islam dan budaya Jawa dalam hal genealogi budaya, mistisisme Islam, orientasi pengajaran Islam tradisional, dan konsepsi kekuasaan di keratonkeraton Jawa. Karena praktek kejawen dapat dijustifikasi sesuai dengan praktek mistisisme Islam, maka tipologi hubungan antara Islam dan budaya Jawa tidak bertentangan tetapi bersifat dialektis.